Determinants of Intravascular Resistance in Indian Diabetic Nephropathy Patients: A Hospital-Based Study - Anubhav Thukral; Manish Mishra; Vaibhava Srivastava; Hemant Kumar; Amit Nandan Dhar Dwivedi; Ram Chandra Shukla; Kamlakar Tripathi (International Journal of Vascular Medicine)
Aims and Objectives. Metabolic dysregulation has failed to explain clinical variability of patients with diabetic nephropathy and hence a renewed interest emerged in haemodynamic factors as determinant of progression and development of diabetic nephropathy. We therefore studied for various factors which can correlate with raised renal vascular resistance in diabetic nephropathy. Material and Methods. Renal vascular resistance was measured in patients with established and incipient diabetic nephropathy and compared with controls using noninvasive color Doppler examinations of intrarenal vasculature. Results. Renal vascular resistance correlated with age, duration of disease, GFR, serum creatinine, and stage of retinopathy. Renal vascular resistance was significantly reduced in patients on treatment with RAAS inhibitors and insulin, than those on OHA and antihypertensives other than RAAS inhibitors. Conclusion. The study implies that renal vascular resistance may help identify diabetics at high risk of developing nephropathy, and these set of patients could be candidates for RAAS inhibition and early insulin therapy even in patients without albuminuria.